The social functions of the Galombang Dance in the dynamics of Minangkabau community life in Padang City - Vinna Aulya; Frendy Satria Palindo; Venny Rosalina; Robby Ferdian; Fabio Yuda (Priviet Social Sciences Journal, 2025)
This study aims to explain the social functions of the Galombang Dance within the dynamics of the Minangkabau community life in Padang City. The Galombang Dance serves not only as a form of entertainment or aesthetic expression but also as a sociocultural medium that reflects traditional values, communal solidarity, and respect for guests. This research employed a qualitative method, with data collected through observations, interviews, and documentation. The data were analyzed descriptively and analytically using an interpretive approach to understand the social and cultural meanings embedded in the performance of the Galombang Dance. The findings reveal that the Galombang Dance functions to strengthen community solidarity, reaffirm Minangkabau cultural identity, and adapt to ongoing social changes. Although its forms and modes of presentation have undergone transformation, the traditional values and social functions it embodies continue to be preserved by the supporting community. Thus, the Galombang Dance can be understood as a form of living local wisdom that remains adaptive to contemporary developments.